Organizacja obrony narodowej w wybranych państwach. Analiza porównawcza Estonii, Finlandii i Rosji: Organization of national defence in selected countries. comparative analysis of Estonia, Finland And Russia - Staśkiewicz, Urszula (Przegląd Wschodnioeuropejski, 2021)
This publication is the result of research into the organization of national defence in selected European countries. The main research problem was to find the answer to the question how the national defence is organized in countries with different geopolitical possibilities, as well as various financial, human and natural resources. The aim of the investigations was to present the defence policy of selected European countries and generate a better understanding of the issues of national defence, including the issue of defence preparations. In order to achieve the goal and solve the research problem, three non-reactive test methods were used: content analysis, existing data analysis and comparative analysis. We decided to select Estonia, Finland and Russia as units of our analysis.